Effect of natural polymer materials on skin healing based on internal wound microenvironment: a review - Yang, Ying; Li, Bingbing; Wang, Mengxin; Pan, Shicong; Wang, Yu; Gu, Jinhui (Frontiers in Chemistry, 2023)
The concept of wound microenvironment has been discussed for a long time.However, the mechanism of the internal microenvironment is relatively little studied.Here, we present a systematic discussion on the mechanism of natural polymer materials such as chitosan, cellulose, collagen and hyaluronic acid through their effects on the internal wound microenvironment and regulation of wound healing, in order to more comprehensively explain the concept of wound microenvironment and provide a reference for further innovative clinical for the preparation and application of wound healing agents.